Pediatric medication management barriers faced by providers serving underserved populations and proposed solutions - Rungvivatjarus, Tiranun; Huang, Maria Z.; Winckler, Britanny; Fisher, Erin S.; Rhee, Kyung E. (Frontiers in Health Services, 2025)
BackgroundWhile families with limited English proficiency and/or low health literacy face increased risks of medication errors, poor medication management, and non-adherence, little is known about the barriers pediatric medical providers experience when educating families on medication use and compliance. This study explores provider-reported barriers and proposed solutions to improving medication management.MethodsFocus group discussions were selected to obtain data as they can provide rich insight into participants’ perspectives. From December 2019 to September 2020, focus group discussions were conducted with pediatric providers from four clinics located in Medically Underserved Areas/Medically Underserved Populations/or Health Professional Shortage Areas, which are geographic areas/populations with limited primary care access. Initially held in person, focus groups shifted to virtual formats during the COVID-19 pandemic. Two investigators independently coded each focus group in an iterative process and worked with a third investigator to discuss and refine emergent themes via inductive thematic analysis.ResultsSixteen providers participated across four focus groups. Four major themes were reported as barriers: (1) time constraints, (2) provider's lack of medication and logistical knowledge, (3) incomplete or absent patient medication information, and (4) complexity/inefficiency of the electronic health records system (EHR). Providers identified three possible solutions to such barriers: (1) EHR optimization or technology tools, (2) dedicated medication educators, and (3) video/graphic tools.ConclusionPediatric providers face barriers in supporting families with medication management including lack of time, knowledge, information, effective EHR. Proposed solutions such as improved technology, dedicated educators, and visual aids may help address these issues while potentially decreasing medication errors.